Legal framework for defining the continental shelf in light of article 76 of the United Nations convention on the law of the sea: A comparative study with the maritime zones law of Saudi Arabia - Abobaker, Mohammed Yahya (International Journal of Innovative Research and Scientific Studies, 2025)
International maritime law relies on coastal governments' continental shelf sovereignty. This law regulates marine resources outside territorial waters. This study compares the Saudi Maritime Zones Law (SMZL) to The United Nations Convention on the Law of the Sea (UNCLOS) Article 76, which establishes the continental shelf. This analysis compares SMZL with UNCLOS legislation, particularly Article 17 and Article 76, which define the continental shelf (CS). The study found a high agreement between Saudi and international law, and Saudi law protects Saudi Arabia's national interests better. Due to SMZL, the Kingdom has exclusive rights to use continental shelf natural resources. The comparative study highlighted how SMZL follows UNCLOS and how Saudi Arabia protects its sovereignty and resources. The research emphasizes aligning Saudi Arabian legislation with international norms, updating local maritime laws to reflect technological advances, and encouraging international cooperation to conserve marine resources. It also emphasizes learning about CS sovereign rights. The findings suggest amending UNCLOS Article 76 to accommodate modern challenges like technological innovation, environmental sustainability, and maritime sovereignty. International cooperation is encouraged to promote fair and sustainable marine resource usage, with national legislative frameworks like SMZL Article 17 supporting international standards.